Non-Magnetic Bimetallic MOF-Derived Porous Carbon-Wrapped TiO2/ZrTiO4 Composites for Efficient Electromagnetic Wave Absorption - Qiao, Jing; Zhang, Xue; Liu, Chang; Lyu, Longfei; Yang, Yunfei; Wang, Zhou; Wu, Lili; Liu, Wei; Wang, Fenglong; Liu, Jiurong (Nano-Micro Letters, 2021)
Modern communication technologies put forward higher requirements for electromagnetic wave (EMW) absorption materials. Metal–organic framework (MOF) derivatives have been widely concerned with its diverse advantages. To break the mindset of magnetic-derivative design, and make up the shortage of monometallic non-magnetic derivatives, we first try non-magnetic bimetallic MOFs derivatives to achieve efficient EMW absorption. The porous carbon-wrapped TiO2/ZrTiO4 composites derived from PCN-415 (TiZr-MOFs) are qualified with a minimum reflection loss of − 67.8 dB (2.16 mm, 13.0 GHz), and a maximum effective absorption bandwidth of 5.9 GHz (2.70 mm). Through in-depth discussions, the synergy of enhanced interfacial polarization and other attenuation mechanisms in the composites is revealed. Therefore, this work confirms the huge potentials of non-magnetic bimetallic MOFs derivatives in EMW absorption applications. Highlights: 1 Non-magnetic bimetallic MOF-derived porous carbon-wrapped TiO2/ZrTiO4 composites are firstly used for efficient electromagnetic wave absorption. 2 The electromagnetic wave absorption mechanisms including enhanced interfacial polarization and essential conductivity are intensively discussed.